Association between weight change across adulthood and risk of chronic kidney disease: NHANES 1999–2020 - Xunliang Li; Mengqian Liu; Qihui Ye; Jiaxin Zhu; Wenman Zhao; Haifeng Pan; Deguang Wang (Renal Failure)
Background Obesity is a recognized risk factor for chronic kidney disease (CKD), but whether weight change is associated with CKD remains unclear. This research aimed to investigate the relationship between weight change patterns across adulthood and the risk of CKD.Methods Data for 34,187 adults participating in the National Health and Nutrition Examination Survey 1999–2020 were analyzed. The weight change patterns of participants were assessed across different time intervals, including transitions from obesity to non-obesity, non-obesity to obesity, and remaining stable obesity. Absolute weight changes were also analyzed, categorizing participants into various weight gain and loss groups. Furthermore, stratified analyses were conducted to explore potential interactions between age, sex, and smoking status about CKD risk.Results The study found that individuals transitioning from obesity to non-obesity, non-obesity to obesity, and remaining stable obesity had an elevated risk of developing CKD throughout adulthood compared to those maintaining stable non-obesity weight patterns. Moreover, a J-shaped or U-shaped relationship was observed between CKD risk and absolute weight changes, with both extreme weight gain (≥20 kg) and substantial weight loss (>2.5 kg) associated with increased CKD risk. Stratified analyses revealed that age and sex played significant roles in these associations, with stronger effects observed among participants under 60 years at baseline.Conclusions This study underscores the link between weight change across adulthood and the risk of CKD. Maintaining a stable weight and avoiding extreme weight fluctuations may reduce CKD risk. These insights can be considered when developing CKD prevention and management strategies.